Analysis of Science Laboratory Readiness for Science Learning at SMP Muhammadiyah Waipare - Badhe, Klemensia; Sani, Yulimira Safriati.Y.M; Fitriah, Fitriah (Lembaga Riset Mutiara Akbar NOMOR AHU-0003295.AH.01.07 TAHUN 2021, 2023)
This study aims to determine: the readiness of the science laboratory to support science learning at SMP Muhammadiyah Waipare. The formulation of the problem in this study is. Readiness of science laboratories in supporting science learning at SMP Muhammadiyah Waipare and what factors influence the utilization of science laboratories at SMP Muhammadiyah Waipare. The purpose of this study was to determine the readiness of science laboratories for science learning at SMP Muhammadiyah Waipare. This type of research is descriptive qualitative research. The data sources in this study consist of primary data sources and secondary data sources. Primary data sources are the main data obtained directly from research subjects, namely teachers, laboratory heads, and also students. Secondary data is data that is supportive in research in the form of documentation, archives from the school and related records from the school. Data collection techniques used in this study were interviews, observation, documentation and questionnaires. The data were analyzed using descriptive descriptions. Based on the results of the research, it was concluded: Readiness of the Science Laboratory for Science Learning at SMP Muhammadiyah Waipare is used as a place to carry out practicum, a place to prepare tools and materials, and is also replaced with a room for learning. The Readiness of the Science Laboratory for Science Learning at SMP Muhammadiyah Waipare is good in terms of the facilities and infrastructure available at SMP Muhammadiyah Waipare. The design of the Science Laboratory is considered good, because it already has a practicum room